2007
DOI: 10.1016/j.febslet.2007.03.023
|View full text |Cite
|
Sign up to set email alerts
|

RNA recognition mechanism of eukaryote tRNA (m7G46) methyltransferase (Trm8–Trm82 complex)

Abstract: Yeast tRNA (m 7 G46) methyltransferase contains two protein subunits (Trm8 and Trm82). To address the RNA recognition mechanism of the Trm8-Trm82 complex, we investigated methyl acceptance activities of eight truncated yeast tRNA Phe transcripts. Both the D-stem and T-stem structures were required for efficient methyl-transfer. To clarify the role of the D-stem structure, we tested four mutant transcripts, in which tertiary base pairs were disrupted. The tertiary base pairs were important but not essential for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…The final structure was in good agreement with experiments measuring the methyl acceptance activities of eight truncated or mutated tRNA transcripts by both Trm8/Trm82 or by bacterial Aquifex aeolicus TrmB (AeTrmB) (Matsumoto et al, 2007). However, no single model showed both an entirely satisfactory interaction between the protein surface and the RNA, indicating that large structural changes probably occur and involve bending of the RNA anticodon stem.…”
Section: Small Angle X-ray Scattering (Saxs)supporting
confidence: 61%
“…The final structure was in good agreement with experiments measuring the methyl acceptance activities of eight truncated or mutated tRNA transcripts by both Trm8/Trm82 or by bacterial Aquifex aeolicus TrmB (AeTrmB) (Matsumoto et al, 2007). However, no single model showed both an entirely satisfactory interaction between the protein surface and the RNA, indicating that large structural changes probably occur and involve bending of the RNA anticodon stem.…”
Section: Small Angle X-ray Scattering (Saxs)supporting
confidence: 61%
“…G46) to be modified (14). Furthermore, we investigated the RNA recognition mechanism of the yeast enzyme (Trm8–Trm82 complex) and found that yeast Trm8–Trm82 has more stringent recognition requirements for the tRNA molecule than A. aeolicus TrmB (15). Thus, protein structure–function relationship studies have been useful in the elucidation of the RNA recognition mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Other enzymes require both subunits for tRNA binding, as is the case with Trm6 and Trm61, although Trm6 is the catalytic component (Anderson et al 1998(Anderson et al , 2000Ozanick et al 2007;Guy and Phizicky 2014;Hori 2014;Swinehart and Jackman 2015;McKenney et al 2017). In yet another instance, the enzymes Trm8 and Trm82, which methylate tRNA to form m 7 G at position 46, are both required to form an active enzyme complex (Alexandrov et al 2002;Matsumoto et al 2007;Leulliot et al 2008;Guy and Phizicky 2014;Hori 2014;Swinehart and Jackman 2015;McKenney et al 2017) We previously demonstrated that two different enzymes, a methyltransferase and a deaminase, converge on a single anticodon loop nucleotide position to catalyze formation of m 3 C and m 3 U at position 32 of tRNA Thr . Unlike many of the aforementioned multiprotein enzymes, we show here that TbADAT2/3 and TbTrm140 are both capable of binding tRNA directly; however, binding individually is nonproductive, leading to neither methylation nor deamination of position 32 of tRNAs; their intended target.…”
Section: Discussionmentioning
confidence: 99%